A Hardware-in-the-Loop Prototype to design Benchmarks for Automation and Control Education. Issue 2 (2020) - Castilla, M.; Rodríguez, F.; Álvarez, J.D.; Donaire, J.G.; Ramos-Teodoro, J.
Abstract: At present, most of the systems which can be found in an industrial environment present both sequential (discrete) or mixed (continuous and discrete) dynamics that must be controlled, monitored and supervised. For this reason, studying these systems and how they can be controlled is a crucial issue which should be covered in engineering education. This article presents a Hardware-in-the-Loop prototype which can be used for automation and control training. This prototype allows teachers to design, in an intuitive manner, different benchmarks to be solved by students in laboratory practice sessions. These benchmarks can be easily adapted to the level and the area of knowledge of students. An example of benchmark has been proposed and commented. Moreover, students' opinion regarding a preliminary version of the prototype has been included and discussed.